ERYSTYKA W PRAKTYCE PRAWNICZEJ - Zeidler, Kamil (Wydział Prawa i Administracji UAM, 2009)
The rhetoric, eristic and negotiating competences of lawyers develop through the whole period of their professional activity. Skills of rhetoric and eristic are of key importance not only in the courtroom but also in other profession-related situations, for instance in negotiations. Therefore, it is important to note that eristic is present in judicial as well as non-judicial legal practice. Every person who participates in a communication process on a daily basis applies many eristic methods, although in most cases stays unaware of that fact, does it intuitively. It is crucial, however, when acting professionally, not to act intuitively but in accordance with acquired and deeply-rooted knowledge. This should then help not only in a more effective application of eristic in one’s own actions, but, above all, in foiling eristic actions of the opponent in a dispute. The paper is an attempt to explain the contemporary status of eristic, particularly in its relation to rhetoric, as well as to point to the ethic controversy concerning its application which proves to be a very important issue especially in a courtroom situation. Finally, the paper provides examples that illustrate the actual extent of eristic application in legal practice. As far as the subject is concerned, Die eristische Dialektyk by Arthur Schopenhauer is frequently cited in the paper because its contemporary practical meaning cannot be ignored.
ERISTIC IN LEGAL PRACTICE